Genetic, social, and environmental risk factors in rheumatoid arthritis-associated interstitial lung disease - Wheeler, Austin M.; Baker, Joshua F.; Poole, Jill A.; Ascherman, Dana P.; Yang, Yangyuna; Kerr, Gail S.; Reimold, Andreas; Kunkel, Gary; Cannon, Grant W.; Wysham, Katherine D.; Singh, Namrata; Lazaro, Deana; et al. (Seminars in arthritis and rheumatism, 2022)
MUC5B and TOLLIP single nucleotide polymorphisms (SNPs) and cigarette smoking were associated with rheumatoid arthritis-interstitial lung disease (RA-ILD) in a predominantly Northern European population. We evaluated whether RA-ILD is associated with these genetic variants and HLA-DRB1 shared epitope (SE) alleles in a large RA cohort stratified by race and smoking history. HLA-DRB1 SE alleles and MUC5B rs35705950 and TOLLIP rs5743890 SNPs were genotyped in U.S. veterans with RA. ILD was validated through medical record review. Genetic associations with ILD were assessed in logistic regression models overall and in subgroups defined by race and smoking status, with additive interactions assessed by the relative excess risk of interaction (RERI). Of 2,556 participants (88% male, 77% White), 238 (9.3%) had ILD. The MUC5B variant was associated with ILD (OR 2.25 [95% CI 1.69, 3.02]), whereas TOLLIP and HLA-DRB1 SE were not. The MUC5B variant was less frequent among Black/African American participants (5.8% vs. 22.6%), though its association with RA-ILD was numerically stronger (OR 4.23 [1.65, 10.86]) compared to all other participants (OR 2.32 [1.70, 3.16]). Those with the MUC5B variant and a smoking history had numerically higher odds of ILD (OR 4.18 [2.53, 6.93]) than non-smokers (OR 2.41 [1.16, 5.04]). Additive interactions between MUC5B-race and MUC5B-smoking were not statistically significant. In this large RA cohort, the MUC5B promoter variant was associated with >2-fold higher odds of RA-ILD. While this variant is less common among Black/African American patients, its presence in this population carried >4-fold higher odds of RA-ILD.